Ganiyeva, Sachli - (:unkn) unknown (My University, 2026)
Saçlı Abdulkhag gizi Ganiyeva graduated with honors from the Moscow Institute of Geodesy, Aerial Photography and Cartography Engineers (MIIGAiK) in 1985, specializing in Astronomical Geodesy. She was among the Azerbaijani specialists who received higher education in major cities of the former USSR through an initiative of National Leader Heydar Aliyev. During her studies, she worked as a laboratory assistant at MIIGAiK and subsequently continued her professional career at the Far Eastern (South Sakhalin) Scientific Center of the USSR Academy of Sciences, in the Laboratory of Modern Movements of the Earth’s Crust. After graduation, she worked as an engineer-geodesist, design engineer, and Head of the Department for the Application and Functionalization of Geodetic Issues at the State Geodesy and Cartography Enterprise. Since 1995, Dr. Ganiyeva has been working at the Azerbaijan University of Architecture and Construction (AzUAC), initially as a Senior Lecturer at the Department of Engineering Geodesy, now the Department of Geomatics. In 2003, she defended her PhD dissertation on “Study of the Evolution of the Parameters of the Earth’s Level Surface” in the specialty of Astrophysics and Radio Astronomy at Baku State University. Since 2005, she has served as an Associate Professor and Head of the Department of Geomatics. Dr. Ganiyeva is the author of 214 scientific and educational works, including 99 scientific articles, 74 conference papers, 18 theses, 12 methodological manuals, 6 collections of course programmes, one monograph, two textbooks, and two teaching aids. In 2016, by Decree No. 2116 of the President of the Republic of Azerbaijan, she was awarded the honorary title of “Honored Teacher”. Her current research focuses on high-precision satellite geodesy networks in Azerbaijan, the Earth’s shape and dimensions, its gravitational field and structure, and the study of the Earth’s evolution using GPS satellite measurement technologies.